Bis(3-bromo-1-oxidoanthraquinone-κ2O1,O 9)-bis(pyridine-κN)zinc(II) - Basirun, Wan Jefrey; Ng, S.W.; Ali, H.M.; Halim, S.N.A.; Koushik, S.; Lajis, N. (International Union of Crystallography, 2005)
The Zn atom in the title compound, [Zn(C14H6BrO 3)2-(C5H5N)2], lies on a centre of inversion. It is chelated by the bromo-substituted hydroxyanthroquinone molecule and is coordinated by the pyridine molecules in an all-trans octahedral geometry. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.